Clinicopathological characteristics of biliary neuroendocrine neoplasms: a multicenter study. (3rd April 2017) - Lee, Kyong Joo; Cho, Jae Hee; Lee, Sang Hyub; Lee, Kwang Hyuk; Park, Byung Kyu; Lee, Jun Kyu; Woo, Sang Myung; Ryu, Ji Kon; Lee, Jong Kyun; Kim, Yeon Suk; Kim, Jae Woo; Lee, Woo Jin
Abstract: Objectives: This study assessed the clinicopathological features, therapeutic approaches, and prognosis of patients with biliary neuroendocrine neoplasm (NENs). Materials and methods: Multicenter retrospective study of patients with biliary tract NENs in the gallbladder, the extrahepatic bile duct, or the ampulla of Vater between 2005 and 2014. Results: Total of 43 patients were included in the study. The median age was 62 years (range: 29–84 years) and 58.1% of the patients were male. The tumors occurred in the gallbladder ( n  = 11), the extrahepatic bile duct ( n  = 5) or the ampulla of Vater ( n  = 27). The liver was the most common metastatic site. Based on the 2010 World Health Organization classification, more patients with gallbladder NENs (11/11 (100%)) had neuroendocrine carcinoma G3 than those with NENs in the ampulla of Vater (10/27 (37.1%)). The median progression free survival time (39.3 vs 5.1 months, p  = 0.001) and median overall survival time (46.9 vs 7.9 months, p  < 0.001) were significantly longer in patients with ampulla of Vater NENs than gallbladder NENs. A 2010 World Health Organization classification of neuroendocrine carcinoma G3 was independently related to poor overall survival (hazard ratio (HR), 27.1; 95% confidence intervals (CI), 2.81-260.68; p  = 0.004). Conclusion: The 2010 World Health Organization classification of neuroendocrine carcinoma G3 was the only factor related to poor prognosis in patients with biliary neuroendocrine neoplasms.